PENDIDIKAN ISLAM INKLUSIF DALAM MASYARAKAT MULTIKULTURAL DI KUPANG - M. Zainul Hasani Syarif; Gunawan Ikhtiono; Muhyani; Chofifah Intan Hornariswari (Jurnal Manajemen Pendidikan Islam Al-Munadzomah, 2026)
This study examines the development and progress of inclusive Islamic education, as reflected in the movement carried out by the Muhammadiyah University of Kupang (UMK) which shows an open attitude in pluralistic social life. UMK remains the most popular Islamic university for both Muslims and non-Muslims, making it one of the leading universities. The educational policies implemented aim to attract public attention through physical facilities, academic quality assurance, student intelligence, introduction of the concept of comprehensive education, and building relationships. The community sends their children to study at Islamic educational institutions regardless of religious identity, even though the majority religion in Kupang is Christian. The approach that teaches universal knowledge without prioritizing a particular religious identity encourages the community to study the teachings of other religions